2015
DOI: 10.1186/s13028-016-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological patterns of Actinobacillus pleuropneumoniae, Mycoplasma hyopneumoniae, Pasteurella multocida and Streptococcus suis in pig herds affected by pleuritis

Abstract: BackgroundRespiratory illness is traditionally regarded as the disease of the growing pig, and has historically mainly been associated to bacterial infections with focus on Mycoplasma hyopneumoniae and Actinobacillus pleuropneumoniae. These bacteria still are of great importance, but continuously increasing herd sizes have complicated the scenario and the influence of secondary invaders may have been increased. The aim of this study was to evaluate the presence of A. pleuropneumoniae and M. hyopneumoniae, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
4
14
0
1
Order By: Relevance
“…The present study agrees with the previously described debilitating effect of growing herd size on prevalence of pleuritis [5,6,7,14,16]. This effect could be related to infection pressure because bigger herds are more likely to need to purchase more animals, which is accompanied by an increased risk of introducing pathogens or naïve animals into the herd.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study agrees with the previously described debilitating effect of growing herd size on prevalence of pleuritis [5,6,7,14,16]. This effect could be related to infection pressure because bigger herds are more likely to need to purchase more animals, which is accompanied by an increased risk of introducing pathogens or naïve animals into the herd.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the timing of the infection remains unknown in our study, as we are dealing with endemic disease. For example, Wallgren et al [5] found different serological patterns during the growing time of pigs in four herds. They showed that repetitive sampling helped to pinpoint the actual causative agent and disease pattern in different herds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This facilitated recirculation of disease and a higher and earlier risk of exposure to pathogens [34] compared with pigs in ow 1, due to contact between animals of different ages and mixed immune status [40]. Actinobacillus pleuropneumonia circulates in the herd for long periods of time [5], with antibody levels increasing with age [41]. Therefore, the higher antibody levels for App from pigs in ow 2 and ow 3 could be associated with direct and prolonged exposure to recovered sick pigs [27] that could still be carrying and shedding pathogens [42].…”
Section: Discussionmentioning
confidence: 99%
“…Also, swine in uenza virus (SIV) has been noted to have an association with pleurisy [10]. Especially dorsocaudal pleurisy has been reported to be strongly associated with APP [1,6,10,11].…”
Section: Introductionmentioning
confidence: 99%